MINI REVIEW: ADSORPSI NANOPARTIKEL ALUMINIUM OKSIDA (Al2O3) TERHADAP ZAT WARNA ORGANIK SINTETIK - Sapira, Putri Abelia; Hiyahara, Irfan Ashari (PROSIDING SEMINAR KIMIA, 2025)
Aluminum oxide (Al2O3) nanoparticles are a strong and versatile material with good mechanical strength, large specific surface area, and high adsorption capacity, making it very favorable for adsorption processes. In addition, aluminum oxide is non-toxic, easy to use, and has good chemical stability. The presence of many hydroxide groups on Al2O3 nanoparticles increases their ability as adsorbents. Therefore, aluminum oxide has attracted widespread attention in the removal of pollutants from the environment, such as heavy metals, pigments, dissolved organic materials, antibiotics, and dyes. This mini review examines the latest developments regarding the use of Al2O3 nanoparticles as adsorbents for synthetic organic dyes, both cationic and anionic, such as Methylene Blue, Orange G, Acid Orange 7, and Eriochrom Black T. The discussion focuses on the efficiency and potential applications of Al2O3 nanoparticles in dye adsorption. Keywords: Adsorption, Al2O3 Nanoparticles, Dyes